DEVELOPMENT OF EDUCATIONAL MONOPOLY WITH WEST JAVANESE CULTURAL CONTENT AS AN EFFORT TO CHARACTER EDUCATION - Sudarmansyah, Ranu; Arifin, Muh. Husen; Kusnadi, Uus; Sutisna, M. Ridwan; Zahirah, Salwa Naurah; Apriyani, Nurhalizah (The Indonesian Journal of Social Studies, 2025)
This study aims to develop an educational monopoly game containing West Javanese culture (Motekar) as an effort to build character, Sundanese cultural literacy, and financial literacy among the younger generation. The low level of understanding among the younger generation of local culture and the lack of awareness of the importance of financial literacy in everyday life form the background of this study. Monopoly games with local wisdom content are an educational and interactive learning medium that can hone students' cultural and financial literacy skills, thereby fostering positive character traits. Using the Research and Development (R&D) approach according to Borg and Gall, this research began with problem identification, literature review, product development, product testing, and product dissemination and implementation. The research questions cover the steps in developing the monopoly media, expert validation, and students' perceptions of the Motekar game. The Motekar game media is expected to not only improve students' understanding of Sundanese cultural and financial literacy but also encourage the formation of positive character in students through regional language and culture learning in line with the principles of education for sustainable development (ESD) in terms of education quality. In addition, Motekar media also has a novel concept and content. In terms of content, Motekar presents a variety of cultures from West Java, while in terms of concept, Motekar presents a strength-based approach so that in the game there are no negative rules such as “going to jail without a specific mistake”.